2010
DOI: 10.1002/hep.23941
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone attenuates age- and diet-associated nonalcoholic steatohepatitis in male low-density lipoprotein receptor knockout mice

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common complication of obesity that can progress to nonalcoholic steatohepatitis (NASH), a serious liver pathology that can advance to cirrhosis. The mechanisms responsible for NAFLD progression to NASH remain unclear. Lack of a suitable animal model that faithfully recapitulates the pathophysiology of human NASH is a major obstacle in delineating mechanisms responsible for progression of NAFLD to NASH and, thus, development of better treatment strategies. We ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 29 publications
5
76
0
Order By: Relevance
“…22,23 LDLR or ApoE single-knockout mice developed some of the NAFLD characteristics [24][25][26] but generally failed to broadly reflect the whole spectrum of NAFLD key features. As such, ApoE À / À mice on a fat-and cholesterol-enriched diet developed hepatic inflammation but only mild steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 LDLR or ApoE single-knockout mice developed some of the NAFLD characteristics [24][25][26] but generally failed to broadly reflect the whole spectrum of NAFLD key features. As such, ApoE À / À mice on a fat-and cholesterol-enriched diet developed hepatic inflammation but only mild steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Histological and biochemical analysis Paraffin-embedded liver sections were stained with periodic acid-Schiff, hematoxylin and eosin. The assessment of NAFLD was previously described [19] . The serum insulin level was measured using a mouse ELISA kit (CUSABIO) according to the manufacturer's instructions.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…However, there are very limited options to prevent NASH and NAFLD at this point. One potential group of drugs, the PPARγ ligands, such as rosiglitazone and pioglitazone, is reported to prevent NASH in animal models and in human patients (9,10,15). PPARγ ligands decrease steatosis through the inhibition of the activation of inflammatory and fibrotic genes, probably due to a decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the PIVENS trial demonstrated an improvement in NASH histology with either vitamin E or an insulin-sensitizing peroxisome proliferator-activated receptor-γ (PPARγ) ligand (9). Consistently, rosiglitazone was also found to attenuate the histological findings and decreased elevated serum enzyme levels in a NASH mouse model (10). In addition, a PPARα agonist, bezafibrate, is known to prevent NASH in animal models (11).…”
Section: Introductionmentioning
confidence: 95%